Preliminary analysis of market potential for a hydropneumatic ground-level integrated diverse energy storage system. (15th May 2019) - Chen, Yang; Odukomaiya, Adewale; Kassaee, Saiid; O'Connor, Patrick; Momen, Ayyoub M.; Liu, Xiaobing; Smith, Brennan T.
Highlights: First volume-control based operation model is proposed for Hydropneumatic storage. Bilinear volume-pressure relationship is linearized by bilinear McCormick Envelope. Real-time prices are used to estimate storage potential with different objectives. Regulation service may contribute as high as 90% in total revenue for some markets. Abstract: With the increasing share of renewable energy in the power grid, energy storage is considered a viable and effective solution to mitigate intermittency and improve power system stability. To quantify and estimate market potential for a recently developed Ground-Level Integrated Diverse Energy Storage (GLIDES) technology, the first operation model is developed for this hydropneumatic system and the bilinear pressure-volume terms are then linearized using the binary McCormick Relaxation method to improve solving efficiency. Based on up-to-date 5-min price data in four different real-time markets, several sets of experiments have been designed with three objective scenarios: maximize arbitrage, maximize arbitrage + reserve, maximize arbitrage + reserve + regulation. The experimental results show that the monetary value of GLIDES could be boosted by participation in ancillary markets and that regulation service might contribute more than half of the total revenue, even as high as 90% in PJM and ISONE markets. In addition, a case study for 1-day operation is used to illustrate the volume control of the GLIDES system.